Letter - Brind, Paul H.
025a-0007-001 MJH Telephone: Holborn 8454 MINISTRY OF LABOUR AND NATIONAL SERVICE. Please address reply (if any) to THE SECRETARY, quoting letter and number A.R.2443/40. International Labour Branch, Hanway House, Red Lion Square, London W.C.1 Your Ref: HVT/AC/DT/64 International Dept. 24th January, 1941. Dear Mr. Carthy, With reference to your telephone message of yesterday, I have turned up the papers relating to Spanish seamen and I assume that the ones to which you are referring are those contained in a long list sent to Mr Scott by Mr Tewson on the 7th November. I have now got a report on most of them and hope to let you have a good deal of information in the course of the next day or two. Yours sincerely PAUL H. BRIND The Secretary Trade Union Congress Transport House, S.W.1. 292/946/25a/7